Switching phenomena in magnetic vortex dynamics - Gaididei, Y.B.; Kravchuk, V.P.; Mertens, F.G.; Sheka, D.D. (Физика низких температур, 2008)
Amagnetic nanoparticle in a vortex state is a promising candidate for the information storage. One bit of
information corresponds to the upward or downward magnetization of the vortex core (vortex polarity). Generic
properties of the vortex polarity switching are insensitive of the way how the vortex dynamics was excited:
by an ac magnetic field, or by an electrical current. We study theoretically the switching process and
describe in detail its mechanism, which involves the creation and annihilation of an intermediate vortex-
antivortex pair.